ANALISIS PENGARUH KEMISKINAN, EKSPOR DAN IMPOR TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA 1991-2020 - Trisnawati, Ike; Prasetyanto, Panji Kusuma (Jurnal Kajian Ekonomi dan Kebijakan Publik (JEpa); Vol 7 No 2 (2022): Jurnal Kajian Ekonomi dan Kebijakan Publik (JEpa), 2022)
This study analyzes the factors that influence economic growth for the period 1991-2020. The dependent variable in this research is economic growth (GDP) and the independent variable consists of poverty, exports and imports. This study uses time series data from 1991-2020. The method used is the Error Correction Model (ECM) which aims to determine the existence of long-term and short-term relationships that occur in each variable. From the research results, it is known that exports and imports in the short and long term have no significant effect on economic growth. While poverty in the long term and short term has a significant influence on economic growth.